Strategy of Personnel Management and the Issue of Its Development in the System of Public Administration of RA - Altunyan, Katerina (YSU Journal of International Affairs, 2021)
The article analyzes one of the most urgent problems in the public administration of the RA. The main object of research is the strategy of personnel management. In a narrow sense, the problem includes the study of the main approaches and the development of personnel policy. Personnel policy and strategy are interconnected, which presupposes a rethinking of the entire system of public administration in RA. The article also formulates proposals for the implementation of strategic planning of personnel management in RA.